Speech Act Found in The Fault in Our Stars Movie - Made Paras Asri, Ni; Nyoman Muliana, I; Gusti Ayu Agung Dian Susanthi, I (KnE Social Sciences, 2022)
This research discussed about meaning, function, and maxims found in that movie. The theory used in this research was the meaning of speech act theory by (Chaer, 2010), the function of speech act theory by (Searle, 1969), and maxims theory by (Grice, 1989). The data source of this research was The Fault in Our Stars Movie. In collecting the data, the researcher used the observation method and note-taking technique. Data collected were classified based on their meaning, function, and maxims. The results of the analysis were presented by using the informal method. Based on the result of analysis, it was found the meaning of speech act such as locutionary, illocutionary and perlocutionary meanings. The function of speech act that found such as representative, directive, commissive, and expressive functions. The maxims found including maxim of quantity, maxims of quality, maxims of relevancy and maxim of manner in the form of fulfillment or violation. Keywords: meaning of speech act, function of speech act, maxims